Influence of Vanadium 4+ and 5+ Ions on the Differentiation and Activation of Human Osteoclasts - Matthias A. König; Oliver P. Gautschi; Hans-Peter Simmen; Luis Filgueira; Dieter Cadosch (International Journal of Biomaterials)
Background. In the pathophysiology of implant failure, metal ions and inflammation-driven osteoclasts (OC) play a crucial role. The aim of this study was to investigate whether vanadium (V) ions induce differentiation of monocytic OC precursors into osteoresorptive multinucleated cells. In addition, the influence of V ions on the activation and function of in vitro generated OC was observed. Methods. Human monocytes and osteoclasts were isolated from peripheral blood monocytic cells (PBMCs). Exposition with increasing concentrations (0–3 μM) of V4+/V5+ ions for 7 days followed. Assessment of OC differentiation, cell viability, and resorptional ability was performed by standard colorimetric cell viability assay 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenil)-2H-tetrazolium (MTS), tartrate-resistant acid phosphatase (TRAP) expression, and functional resorption assays on bone slides during a period of 21 days. Results. No significant differences were noted between V4+/V5+ ions (p>0.05). MTS showed significant reduction in cellular viability by V concentrations above 3 μM (p<0.05). V concentrations above 0.5 μM showed negative effects on OC activation/differentiation. Higher V concentrations showed negative effects on resorptive function (all p<0.05) without affecting cell viability. V4+/V5+ concentrations below 3 μM have negative effects on OC differentiation/function without affecting cell survival. Conclusion. Vanadium-containing implants may reduce implant failure rate by influencing osteoclast activity at the bone-implant interface. V-ligand complexes might offer new treatment options by accumulating in the bone.